Antimicrobial and antioxidant activity of pulp extracts from three populations of Ziziphus lotus L. Issue 6 (11th November 2019) - Rais, Chaimae; Driouch, Asmae; Slimani, Chaimae; Bessi, Aymane; Balouiri, Mounyr; El Ghadraoui, Lahsen; Lazraq, Abderrahim; Al Figuigui, Jamila
Abstract : Purpose: This paper aims to evaluate the antimicrobial and antioxidant activity of ethanol, methanol and aqueous extracts of the jujube fruit. Design/methodology/approach: The fruit samples were harvested from Ziziphus lotus L. in three regions of Morocco: Aïn Chifae (Immouzer), Saiss (Fez) and Guercif. The fruit extracts were obtained by Soxhlet method using ethanol, methanol and water, and then a phytochemical screening was done for each extract. Total phenolic and total flavonoids contents were also determined. Afterward, the antimicrobial activity of the studied extracts was evaluated using the broth microdilution method. To estimate the total antioxidant effect of these extracts, the DPPH (2, 2-diphenyl-1-picrylhydrazyl) scavenging and phosphomolybdate tests were performed. Findings: Results showed that the highest content of polyphenols and flavonoids was found for ethanol and methanol extracts, while the lowest content was found in the aqueous extracts for all populations studied. Thus, results showed that the highest content of phenolic compounds was recorded in the population of Fez. Methanol extract of this population was the richest in polyphenols (30.36 mg/g) and in flavonoids (13.03 mg/g). The antimicrobial tests showed that Enterococcus faecalis and Pseudomonas aeruginosa were the most sensitive (6.25 mg/ml), compared to the other tested strains. Based on the minimal bactericidal concentrations/minimal fungicidal concentration or MFC/MIC ratio, it seems that ethanol extracts showed a bactericidal effect against Escherichia coli, Staphylococcus aureus and Bacillus subtillis, and a bacteriostatic effect against Enterococcus faecalis. On the other hand, the methanol extract showed bacteriostatic effect against Enterococcus faecalis and Pseudomonas aeruginosa. In addition, methanol extracts of Ziziphus lotus have significant antioxidant potent. Originality/value: Methanol and ethanol extracts of Ziziphus lotus fruit have demonstrated strong antimicrobial effect. Moreover, the authors were able to show that the extract of Ziziphus lotus fruit has a very important antioxidant power.